Transforming Recruitment and Selection Practices in Organizations Through Discriminative and Generative AI Adoption: A Structuration Lens - Dutta, Debolina; Naveen, P. M. (Human Resource Management, 2026)
ABSTRACT The emergence of Artificial Intelligence (AI) has dramatically impacted human decision‐making, productivity, and human agentic role delivery, thereby transforming HRM practices, particularly in recruitment and selection. Traditional recruitment and selection methods involve the dynamic interplay of structure and human agents. This interplay is changing with the emergence of human‐technology‐conjoined agencies that share task delivery and role performance responsibilities, thereby altering and creating new recruitment and selection routines. We conducted an exploratory qualitative study with 43 HR and talent acquisition leaders in a high‐growth emerging market context to understand the transformational role of discriminative and generative AI technology agencies in changing recruitment and selection practices. This study contributes to existing HRM literature by demonstrating the impact of discriminative and generative AI in recruitment and selection and the simultaneous human‐AI collaboration and algorithmic management of humans emerging as a consequence. Furthermore, we theorize the transformational changes in structures and processes across the entire recruitment and selection process emerging from conjoined agencies.